Analisis Pengaruh Promosi Financial Technology (E-Money) Dan Ketersediaan Dana Melalui Gaya Hidup Terhadap Impulsive Buying (Studi Kasus Pada Karyawan Divisi Sparepart - Nila Rahayu; Abdurrahman Abdurrahman; Yeldy Dwi Genadi; Nur Fazillah Milawati (Journal of Economics and Business UBS, 2023)
In the era of globalization, shopping activities are not only for buying goods needed or for fulfilling needs, but shopping has become a lifestyle, pleasure & psychological activity. Not only the promotion of e-money, lifestyle, availability of funds (money availability), it also becomes the basis for consumers to make purchases. This study aims to analyze the effect of financial technology promotion (e-money) and the availability of funds through lifestyles on impulsive buying. The population used in this study are employees of PT. Mitra Pinasthika Mulia Surabaya in the spareparts division and the number of samples of this study were 92 people with a purposive sampling method. This research used PLS as analysis. The results showed that e-money promotion had a negative influence on impulsive buying, e-money promotion had a positive effect on lifestyle, the availability of funds had no effect on impulsive buying, the availability of funds had a positive effect on lifestyle and lifestyle had a positive effect on impulsive buying.